Evaluation of Two Different Treatments for Larch Logs as Substrates to Cultivate Ganoderma tsugae in the Forest - Lei Xia; Xiao Tan; Peng Wang; Dahai Yang; Yang Zhang; Yanru Cui; Ya Yu; Weidong Zhang; Xiao Huang; Jiawei Wen (Life)
Larch wood, a prevalent cultivation medium for Ganoderma tsugae, has yet to be scrutinized concerning the differential impacts of sterilized and non-sterilized substrates on the growth and development of this fungus. Our present investigation sought to elucidate these effects in a forest-like environment. After larch wood segments were sun-dried, they were divided into two groups; one group was bagged and autoclaved, while the other group was bagged without any treatment. Subsequently, all segments were inoculated with the G. tsugae strain HLXL1 and ensconced under the canopy of a Pinus koraiensis forest, thereby approximating the conditions of natural growth. Wild G. tsugae was used as the control. Data on agronomic traits, production days, fruiting body yield, and effective constituent content were analyzed. The results indicated no significant differences between sterilized and non-sterilized substrates in terms of agronomic traits. However, the mineral content and bioactive compounds in G. tsugae fruiting bodies significantly differed across various growth stages. The outcomes were optimal for non-sterilized substrates, followed by sterilized substrates, while the wild strains were markedly less effective than the cultivated ones.